APLIKASI PENYEWAAN PERALATAN CAMPING DAN HIKING PADA PANDANARAN OUTDOOR BERBASIS WEB - Susanto, Susanto; Anggraini, Lila; Kurniawan, Nurdin; Cahyono, Yudi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
Pandanaran outdoor is one of the rental service companies or rental of camping and hiking equipment. However, the lack of use of technology in the process of renting equipment and conveying information about what equipment can be rented on a particular day makes it difficult for customers to carry out the rental process. Pandanaran Outdoor itself still uses manual recording in its rental process. With the advancement of technology and on the basis of the need for transaction management, data management, and information delivery, it is necessary to create a web-based camping and hiking equipment rental application at Pandanaran Outdoor, this website is designed using CodeIgniter, PHP, Visualcode, Bootstrap, Javascript, and MySQL Database. The system method used in this research is the waterfall method, the results obtained are used to describe the sequence of software development processes as a cycle in the flow of making rental applications. The presence of this application is expected to speed up and simplify the process of renting camping and hiking equipment at Pandanaran Outdoor.